Marke, Nachhaltigkeit und Verbraucherpolitik Die Gewährleistungsmarke im Spannungsfeld zwischen Unternehmen, Konsumenten und Regulierung - Boltz, Dirk-Mario; Bruhn, Manfred; Gröppel-Klein, Andrea; Hellmann, Kai-Uwe (Verbraucherforschung, 2022)
The certification mark, which was introduced in response to an EU initiative in 2017, has been available in Germany since 2019. Its main features are neutrality, monitoring/control and transparency for certain material or service promises for which the legal protection of a certification mark is claimed. This anthology explores the questions of how exactly the effect of this instrument is to be assessed, what experiences have already been made with it, and how warranty marks are to be evaluated in terms of brand technology, customer orientation, and consumer policy.